Early Neolithic Settlement of the Po Plain (Northern Italy) - Paolo Biagi; Elisabetta Starnini; Dušan Borić; Niccolò Mazzucco (Documenta Praehistorica, 2020)
Around the mid-19th century, several groups of archaeologists active in northern Italy discovered a few sites characterized by the presence of ‘hut-floors’ or ‘pit-dwellings’ (fondi di capanna), which they attributed to a well-defined period of their Stone Age sequence. Research in the central Po Plain of Lombardy was resumed in the 1970s, allowing one to attribute some of the older discoveries to the Early Neolithic Vhò cultural aspect. The scope of the excavations, which started on one of the Vhò di Piadena sites in 1974, was to interpret the function of the previously discovered features, establish their radiocarbon chronology, and compare the finds with those of the Fiorano culture distributed across the eastern regions of the Po Plain. The main goal of this paper is to provide an international audience with novel information about one of the still poorly known Early Neolithic cultural aspects of northern Italy, namely that of the Vhò.